Operation parameters of a small scale batch distillation column for hydrous ethanol fuel (HEF) production (2015)
Batch distillation applied to hydrous ethanol fuel (HEF) production on a small scale still requires operating conditions that ensure optimal top product quality and productivity. The aim of this study is to statistically validate a batch still through the employment of response surface methodology (RSM). Operational and productivity parameters were formulated in order to guarantee quality compliance with the legal requirements for the top product concentration, besides providing support information to control the production of HEF on a small scale. The reboiler control and dephlegmator temperatures maintained within the range of 97.5 to 99.5°C and 60 to 70°C, respectively, combined with a variable reflux ratio, was satisfactory in obtaining a top product concentration, in accordance with legal regulations, as well as high productivity. The results of this study may contribute to the assembly of a simple and low-cost batch distillation control system.